Structural and immunological principles leading to chemically synthesized, multiantigenic, multistage, minimal subunit-based vaccine development (2011)
Identifying the principles and rules for developing a logical, rational vaccine methodology against various diseases, is discussed. SPf66, the first multiantigenic, multistage, minimal subunit-based, chemically synthesized anti-P. falciparum malaria vaccine. A robust, sensitive, and specific methodology is developed for defining the intimate molecular interactions mediating merozoite invasion of RBC by synthesizing short merozoite-derived protein peptides binding specifically and with high affinity (HABP) to RBCs. Conserved HABP-mediated sporozoite binding to hepatic cells is identified in EBA-175 for developing a multiantigenic, multistage, fully protective antimalarial vaccine. for developing a logical and rational vaccine methodology at the molecular level, monkeys' immune system molecules is analyzed by cloning and sequencing the Aotus genes encoding immunoglobulins, cytokines, and Class I and II molecules.